2017
DOI: 10.3389/fnhum.2017.00201
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on the Effects of Transcranial Direct Current Stimulation on Brain Rhythms and Entropy during Self-Paced Finger Movement using the Epoc Helmet

Abstract: Transcranial direct current stimulation (tDCS) of the cerebellum is emerging as a novel non-invasive tool to modulate the activity of the cerebellar circuitry. In a single blinded study, we applied anodal tDCS (atDCS) of the cerebellum to assess its effects on brain entropy and brain rhythms during self-paced sequential finger movements in a group of healthy volunteers. Although wearable electroencephalogram (EEG) systems cannot compete with traditional clinical/laboratory set-ups in terms of accuracy and chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Furthermore, studies on the effects of cerebellar tDCS on healthy patients have revealed which circuits and functions can be modulated. Similar to DBS, tDCS impacts the cerebellum, the thalamus, the basal ganglia, and the cortex, as measured by the cerebellar brain inhibition (CBI), EEG, and behavioral indices [201204]. For example, tDCS has been shown to modulate CBI in healthy subjects [205].…”
Section: Non-invasive Stimulation In Humansmentioning
confidence: 99%
“…Furthermore, studies on the effects of cerebellar tDCS on healthy patients have revealed which circuits and functions can be modulated. Similar to DBS, tDCS impacts the cerebellum, the thalamus, the basal ganglia, and the cortex, as measured by the cerebellar brain inhibition (CBI), EEG, and behavioral indices [201204]. For example, tDCS has been shown to modulate CBI in healthy subjects [205].…”
Section: Non-invasive Stimulation In Humansmentioning
confidence: 99%
“…The most recent studies show that cerebellar stimulation using continuous theta-burst stimulation (cTBS) is NMDA receptordependent and most likely involves long-term potentiation (LTP) and long-term depression (LTD) [11]. This translates to an altered functional connectivity with remote cortical areas [12], which is also observed after transcranial alternating current stimulation (tACS) [13] and after transcranial direct current stimulation (tDCS) [14]. Although tACS and tDCS modulate cerebellar plasticity and functional connectivity, these electric techniques most likely operate in a different way than the transcranial magnetic stimulation (TMS) techniques such as cTBS [10].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 397 records were identified from the databases and reduced to 57 records after removal of duplicates (Figure 1). Among the 57 records, 52 records were further excluded: 40 records were reviews [6,16,18,19,22,[25][26][27][28][29][30][31][32][33][34], conference proceedings [35][36][37][38][39][40], responses [41,42], editors' notes [43], letters to the editors [44], reports [45], corrections [46], updates [47], theoretical papers [48], commentaries [49,50], book chapters [51], published protocols [52], or clinical trials registration records [53][54][55][56][57][58][59]; two studies did not recruit human participants [60,61]; one study did not recruit patients with cerebellar ataxias [62]; one study did not apply tDCS [63]; three studies used cranial electrotherapy stimulation, CES…”
Section: Resultsmentioning
confidence: 99%